A new method for the row-by-row decoupling problem with pole assignment - Garone, Emanuele; Schmid, Robert; Ntogramatzidis, Lorenzo (2016)
We consider the classic problem of row-by-row input-output decoupling of a linear system by state feedback. We utilise methods from the recent work of two of the present authors to offer a new design method to obtain a feedback matrix that will solve the decoupling problem and also assign a desired set of closed-loop poles.